2010
DOI: 10.1086/654892
|View full text |Cite
|
Sign up to set email alerts
|

Letting Good Opportunities Pass Us By: Examining the Role of Mind-Set during Goal Pursuit

Abstract: It is generally accepted that forming an implementation intention promotes goal pursuit and achievement. Forming an implementation intention encourages people to develop a plan, to prepare for events that allow for the execution of the plan, and to efficiently respond to these opportunities. Yet, forming an implementation intention may not be universally beneficial. An implementation intention may encourage the use of means that are part of the plan but may discourage the use of efficacious means that are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 49 publications
(54 reference statements)
3
57
1
Order By: Relevance
“…Prior research has found, for example, that people are less able to form if-then plans as the number of cues increases (Cohen et al 2008), suggesting that limits on ability can spoil the benefits otherwise afforded by planning. Even if people are able to form specific plans, the benefits associated with automatic responding may be offset by costs to response flexibility (Bayuk et al 2010;Patalano and Seifert 1997). Thus, planning is not always useful and further research is needed to understand (1) when planning can benefit multiple goals and (2) whether the results of our own investigation would generalize to other settings where goal pursuit is complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has found, for example, that people are less able to form if-then plans as the number of cues increases (Cohen et al 2008), suggesting that limits on ability can spoil the benefits otherwise afforded by planning. Even if people are able to form specific plans, the benefits associated with automatic responding may be offset by costs to response flexibility (Bayuk et al 2010;Patalano and Seifert 1997). Thus, planning is not always useful and further research is needed to understand (1) when planning can benefit multiple goals and (2) whether the results of our own investigation would generalize to other settings where goal pursuit is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Although specific planning was ineffective here, other types of planning might facilitate goal attainment in complex settings. For instance, compared to specific plans, loose plans afford greater flexibility (Bayuk et al 2010). Loose plans might facilitate success if these plans are truer representations of how consumers typically think about multiple goals (Vallacher and Wegner 1989) and might not reduce commitment to multiple goals (just as forming goal intentions did not reduce commitment here).…”
Section: Planning Effectively Within a Goal Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Both abstract goals and concrete intentions require shielding from competitive motivational states if they are to be completed (Gollwitzer 1999). Thus Bayuk et al (2010) demonstrate that adopting a plan (e.g., eat fewer eggs to reduce cholesterol) encourages its execution but discourages the execution of alternative, out-of-plan behaviors (e.g., exercise more to reduce cholesterol). Veling and Van Knippenberg (2008) further show that information that competes with intentions gets inhibited.…”
Section: Accessibility Principles Of Motivational Constructs In Memorymentioning
confidence: 92%
“…For example, Aarts and Dijksterhuis (2000) find that the activation of a goal (e.g., "going to the university") leads to the activation of specific behaviors previously performed to attain that goal (e.g., "take the bus"). It is also possible to activate specific intended behavior directly, which might lead to the activation of a related goal (Bayuk, Janiszewski, and Leboeuf 2010;Kruglanski et al 2002), such as priming Lipton iced tea to activate the goal of quenching thirst (Karremans, Stroebe, and Claus 2006). Along similar lines, this research proposes that responding to an intention question is a subtle manipulation that may engender the activation of an intention.…”
Section: Motivational Consequences Of Responding To An Intention Quesmentioning
confidence: 95%